2021
DOI: 10.1177/15910199211019176
|View full text |Cite
|
Sign up to set email alerts
|

Clot-based radiomics features predict first pass effect in acute ischemic stroke

Abstract: Purpose Our aim was to evaluate the performance of clot-based radiomics features (RFs) for predicting first pass effect (FPE) in patients with acute ischemic stroke (AIS). The secondary purpose was to search for any other variables associated with FPE. Materials and methods Patients who underwent mechanical thrombectomy (MT) for anterior circulation large vessel stroke in a single center were retrospectively reviewed. Patients were divided into two groups: FPE and non-FPE. Two observers extracted RFs from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…The recanalization was considered successful when a modified Thrombolysis in Cerebral Infarction (mTICI) score of 2b/3 was documented by DSA, which was recorded during the operation and evaluated by experienced neurologists. Cranial CT was performed within 48 h after the operation to observe whether hemorrhage appeared (8). Symptomatic intracerebral hemorrhage (sICH) was described as hemorrhage accompanying a clinical worsening of ≥ 4 points on the NIHSS score (11).…”
Section: Cfs Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recanalization was considered successful when a modified Thrombolysis in Cerebral Infarction (mTICI) score of 2b/3 was documented by DSA, which was recorded during the operation and evaluated by experienced neurologists. Cranial CT was performed within 48 h after the operation to observe whether hemorrhage appeared (8). Symptomatic intracerebral hemorrhage (sICH) was described as hemorrhage accompanying a clinical worsening of ≥ 4 points on the NIHSS score (11).…”
Section: Cfs Collectionmentioning
confidence: 99%
“…Radiomics analysis is an emerging approach that converts imaging data into a high-dimensional feature space using automatically extracted data-characterization algorithms (6). Several studies have reported that clot-based radiomics is predictive of treatment response after MT strategy for AIS (7)(8)(9)(10). This suggests that the radiomics features (RFs) extracted from pretherapeutic radiological imaging may provide valuable information about the clot composition and structure, which may influence the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that TR could be used to predict reperfusion with IVT,13 first attempt reperfusion,14 and the number of EVT attempts required for successful reperfusion, respectively 12. In contrast to our work, two small single-center studies found that thrombi with a more heterogeneous texture and higher density values were associated with more attempts required for successful reperfusion and a lower chance of first attempt reperfusion 12 14. The higher IVT percentages in our study might have contributed to this difference because our results were in accordance with a previous radiomics study performed in IVT-treated patients 13.…”
Section: Discussionmentioning
confidence: 99%
“…Although potentially valuable, thrombus radiomics (TR) have scarcely been related to recanalization outcomes in patients with acute ischemic stroke 12 13. To date, only two small single-center studies in <100 patients have found an association between TR, first attempt reperfusion, and number of attempts to achieve reperfusion in patients treated with EVT 12 14. It remains unclear how well these findings generalize to other populations, whether TR have an added predictive value compared with clinical variables (CV) and MTM, and whether the effects found on procedural outcomes also affect functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of articles are evaluating AI techniques that analyze the neuroimaging signs of the clot (or thrombus) occluding the arteries in ischemic stroke [13] [14] [15] [16] [17] [18] [19] [20] [21] [22] [23]. No systematic reviews were conducted so far to examine the progress made in developing AI methods that are using clot imaging derived parameters.…”
Section: Introductionmentioning
confidence: 99%